Preferensi Pengguna dalam Penentuan Kriteria Lokasi Infrastruktur Pengisian Daya Kendaraan Listrik di Kota Surabaya - Himawan Ardiansyah; Rulli Pratiwi Setiawan (Jurnal Penataan Ruang, 2025)
Climate change due to greenhouse gas emissions, particularly from the transportation sector, is a serious global challenge. Surabaya, contributing 96% of carbon emissions from this sector, needs the adoption of electric vehicles as a sustainable transportation solution. This study aims to formulate recommendations for electric vehicle charging station location criteria based on user preferences. The method used is randomized conjoint analysis to identify user preferences on factors such as accessibility, waiting time, infrastructure capacity, distance between stations, charging duration, and rates. The results of the preference analysis will inform strategy formulation using the Importance-Based Strategic Formulation approach. The study shows that time efficiency, including both charging duration and waiting time, is the most important factor for selecting charging station locations in Surabaya, while charging tariffs are also a significant consideration. This research contributes to government spatial planning, infrastructure providers in determining optimal locations, and the public in accessing efficient and affordable charging services.